Criticizing Amina Wadud's Views on Leadership in the Household - Syahrudin; Akhmad Hasan Saleh (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Controversial issues regarding the status and standing of women are widely discussed by contemporary Islamic figures. This topic seems to be a hot topic that is rarely discussed. Likewise, household management is given to men, but one of the feminist activists, Amina Wadud Muhsin, rejects this issue. Therefore, this article will focus on the issue of Amina Wadud Muhsin's biography, the meaning of leadership in Islam, and Amina Wadud Muhsin's views on household leadership, to help women's household leadership by Amina Wadud Muhsin. An Islamic feminist scientist and thinker. This research aims to analyze and criticize the concept of women's leadership at home from the perspective of Amina Wadud, an Islamic feminist scholar and thinker. This research aims to explore the understanding of the concept of women's leadership in Amina Wadud's view, especially in the household context, and then compare it with the views of other contemporary scholars such as Buya Hamka, Quraish Shihab and others regarding the role of women in society. The research method used for analysis is descriptive and critical research method analysis, with a focus on Islamic literature and works related to Amina Wadud. The analysis shows that there are differences in views between the concept of modern ulama regarding the role of women in the household and Amina Wadud's view of ensuring gender equality. Amina Wadud Muhsin's study on women's leadership in the household suggests that women can become household leaders if men do not fulfill two conditions. First, what a man gives to his family and what he spends from his wealth to support women. . If one of these conditions is not met and implemented, it is the same as a man not being able to support his wife and family. Amina Wadud emphasized the importance of women's leadership and active participation in the household as a form of empowerment. This study also highlights the challenges and conflicts that can arise when traditional views and progressive views regarding women's roles in the household. This analysis provides detailed insight into the concept of female leadership in Islam and the potential for changes in society's views on the role of women in the household. The results of this research can help stimulate discussion and critical thinking regarding gender issues in Islam and the family, especially in women's leadership positions. Apart from that, this research can also provide a more comprehensive and progressive view regarding the role of women in household management in contemporary Islamic society. This researcher has reached the final stage of the research and really appreciates all input and suggestions from further researchers as well as constructive criticism so that this research can further develop the concept of Kiwama by Amina Wadud in the future.